Day 3 Wed, November 07, 2018 2018
DOI: 10.4043/29145-ms
|View full text |Cite
|
Sign up to set email alerts
|

Deep Recurrent Neural Network DRNN Model for Real-Time Multistage Pumping Data

Abstract: A new real-time model was developed, based on a deep recurrent neural network (DRNN), to predict response variables, such as surface pressure response, during the hydraulic fracturing process. During the stimulation process stage, fluids are inserted at the top of the wellhead, and the flow is driven by the difference between the hydrostatic pressure and reservoir pressure. The major physics and engineering aspects in this process are very complex; quite often, the measured data includes a large amount of unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thanks to advances in computing power and the iterative updating of algorithms, AI has also become a key technology for the intelligent exploration of oilfields. These applications mainly focus on PVT prediction [34][35][36], missing value regression [37], well location prediction [38,39], history matching [40][41][42], and production prediction [43][44][45][46][47][48]. Many studies indicate that AI technology can improve the efficiency and economic benefits.…”
Section: Proportional Divisionmentioning
confidence: 99%
“…Thanks to advances in computing power and the iterative updating of algorithms, AI has also become a key technology for the intelligent exploration of oilfields. These applications mainly focus on PVT prediction [34][35][36], missing value regression [37], well location prediction [38,39], history matching [40][41][42], and production prediction [43][44][45][46][47][48]. Many studies indicate that AI technology can improve the efficiency and economic benefits.…”
Section: Proportional Divisionmentioning
confidence: 99%
“…The authors demonstrated that both networks could capture the interference between multiple wells at the same reservoir. RNN with the long-short-term memory (LSTM) cell [6] was applied in the paper [7] to predict the wellhead pressure during a fracturing treatment, and the input parameters of the network are the surface characteristics of the well. In the papers discussed above, the machine learning models utilize either recurrent or convolutional neural networks.…”
Section: Introductionmentioning
confidence: 99%